Constructing the New Consumer Society
XI, 302 p.
Keywords: This book argues that the coming of the 'a new consumerism' in the affluent societies marks a distinct phase of modernity. Limits of production no longer confine consumption to what is necessary or instrumental. Demands for increasing production no longer shape ideology and culture as they did previously. Important contemporary themes of morality, the body, citizenship and inequality are here placed in a new theoretical light. The book provides examples of new codes of happiness in consuming products, culture and entertainment. Issues of nutrition, consumer policy, environmental risk and health are discussed in the light of these new codes.